2022
DOI: 10.1093/ecco-jcc/jjac029
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Serological Response to COVID-19 Vaccines in Patients with IBD is Further Diminished by TNF Inhibitor Therapy; Early Results of the VARIATION study [VAriability in Response in IBD Against SARS-COV-2 ImmunisatiON]

Abstract: Background and Aims Evidence suggests patients with inflammatory bowel disease (IBD) receiving TNF-antagonists have attenuated response to vaccination against COVID-19. We sought to determine the impact of IBD and various medications for treatment of IBD on antibody responses to vaccination against COVID-19. Methods Patients with IBD (n=270) and healthy controls (HC, n=116) were recruited prospectively and quantitative antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 39 publications
5
19
0
Order By: Relevance
“…In contrast, IBD patients on therapy with vedolizumab and healthy controls did not differ significantly ( p > 0.05) with respect to S-IgG and sVNT inhibition levels. However, our study corroborates previous studies that demonstrated significantly reduced antibody levels in immunocompromised IBD patients compared to healthy controls in the 2–12-week period after second vaccination [ 28 , 33 , 34 , 35 , 36 ]. In particular, patients on anti-TNF therapy showed significantly reduced sVNT inhibitory levels and decreased S-IgG levels [ 33 , 34 , 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, IBD patients on therapy with vedolizumab and healthy controls did not differ significantly ( p > 0.05) with respect to S-IgG and sVNT inhibition levels. However, our study corroborates previous studies that demonstrated significantly reduced antibody levels in immunocompromised IBD patients compared to healthy controls in the 2–12-week period after second vaccination [ 28 , 33 , 34 , 35 , 36 ]. In particular, patients on anti-TNF therapy showed significantly reduced sVNT inhibitory levels and decreased S-IgG levels [ 33 , 34 , 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…In particular, patients on anti-TNF therapy showed significantly reduced sVNT inhibitory levels and decreased S-IgG levels [ 33 , 34 , 37 , 38 , 39 ]. Shebab et al (2021) and Doherty et al (2022) already demonstrated reduced seroconversion rates in patients on anti-TNF medication [ 35 , 40 ]. Patients on vedolizumab did not show impaired humoral immune responses up to 12 weeks after second vaccination compared to healthy controls [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…26 Our data are consistent with previous studies in demonstrating diminished antibody responses following two doses of a SARS-CoV-2 vaccine for patients on anti-TNF therapy, combination immunosuppressive therapies, and corticosteroids. [6][7][8][9][10][11]24,27,28 In contrast, our study showed that the 3 rd dose of the vaccine yielded high antibody titres across all classes of medications used for maintenance of remission in IBD. However, administration of vaccine while concurrently taking prednisone yielded lower antibody response following 1 st , 2 nd , and 3 rd dose of the vaccine.…”
Section: Discussionmentioning
confidence: 84%
“… 6 Regarding corticosteroids, their impact on humoral immunity has been previously suggested. 6 However, no significant attenuating effects were detected by Doherty and colleagues, 4 which may be related to the low number of patients receiving steroids in their study [ n = 10] or to the dosage [not reported]. Concerning anti-TNF therapy, while some studies failed to find any effect on humoral response, 5 others reported an attenuated response in IBD patients under infliximab 2 , 7 and, in contrast to the study by Doherty and colleagues, also detected lower levels of anti-spike IgG in patients under combination therapy.…”
mentioning
confidence: 96%
“…In this issue of the Journal of Crohn’s and Colitis , Doherty and colleagues 4 have published a prospective multi-centre study evaluating how prior SARS-CoV-2 exposure, vaccine class, current IBD-related medication and biomarkers for disease activity impact vaccine response. In their study, 4 the presence of IBD by itself affected humoral immunity, regardless of the use of IBD-related medication. Indeed, the seroconversion rate in IBD patients was 80% and 97% after receiving the first and second doses, respectively, whereas this rate reached 97% and 100% in healthy controls.…”
mentioning
confidence: 99%